1989
DOI: 10.1084/jem.169.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of 178 I-Abm12-reactive T cells.

Abstract: We have studied the genetic diversity of the TCR repertoire to the murine alloantigen I-Abm12 by generating a panel of 178 C57BL/10-derived I-Abm12-reactive T cell hybridomas. The expression of V alpha and V beta gene families was examined in this panel and the frequency of expression of V beta, but not ofV alpha, gene families differed significantly from that observed in a companion panel of random C57BL/10-derived hybridomas. The V beta 5 gene family was expressed significantly less frequently while the V be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 54 publications
5
30
0
Order By: Relevance
“…This is, to our knowledge, the first structural analysis of rearranged TCR genes among human T cell clones in specific responses. Skewed V segment use among alloreactive T cells has also been observed in the mouse (25,(37)(38)(39), but very few V gene sequences were reported in these studies (25).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is, to our knowledge, the first structural analysis of rearranged TCR genes among human T cell clones in specific responses. Skewed V segment use among alloreactive T cells has also been observed in the mouse (25,(37)(38)(39), but very few V gene sequences were reported in these studies (25).…”
Section: Resultsmentioning
confidence: 96%
“…Each of the Vol primers was chosen to match with all members of a given family, but mismatch with other Vf3 families was not required at this stage. Asymmetric PCR amplification was done as previously described (24,25), using 10 nM VQE plus 1 pM C161 oligonucleotides for the generation of the minus strand, and 1 pM Vol plus 10 nM COE oligonucleotides for the generation of the positive strand. Direct sequencing of amplified DNA strands was carried out as described (25), using the corresponding Vol oligonucleotide or the COI oligonucleotide as primers for sequencing the minus or the positive strand, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The low-level T cell response to B6.H-2 bm12 skin and cardiac allografts might be indicative of a restricted repertoire of alloreactive T cells to the I-A bm12 alloantigen. However, rigorous investigation of the TCR repertoires expressed by B6.H-2 bm12 -reactive T cells indicates a diverse population of T cells generated in response to the single class II MHC disparity (40).…”
Section: Figurementioning
confidence: 99%
“…Though different portions of both the α and β chains play integral roles in determining antigen specificity, it is the complementarity-determining 3 region (CDR3) (76) that undergoes somatic recombination of variable (V), diversity (D), and joining (J) genes, along with insertion of nontemplated nucleotides, which leads to the tremendous CDR3 diversity and thus TCR diversity of the millions of T cell clones in an individual (77,78). While most primary peptide antigen-specific immune responses reflect recognition by a small number of TCRs, early studies demonstrated remarkable diversity of Vβ usage contributing to the alloresponse against a single MHC allelic difference, suggesting that the overall alloreactive repertoire was broad (79,80). Similarly, measurement of the distribution of lengths of TCRβ CDR3s, known as spectratyping, confirmed the broad repertoire of alloreactive TCRs (81).…”
Section: Diversity Of Alloreactive Tcrsmentioning
confidence: 99%